2015
DOI: 10.1002/hbm.22768
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ageing on fMRI: Correction for the confounding effects of vascular reactivity evaluated by joint fMRI and MEG in 335 adults

Abstract: In functional magnetic resonance imaging (fMRI) research one is typically interested in neural activity. However, the blood-oxygenation level-dependent (BOLD) signal is a composite of both neural and vascular activity. As factors such as age or medication may alter vascular function, it is essential to account for changes in neurovascular coupling when investigating neurocognitive functioning with fMRI. The resting-state fluctuation amplitude (RSFA) in the fMRI signal (rsfMRI) has been proposed as an index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
212
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(238 citation statements)
references
References 131 publications
(174 reference statements)
26
212
0
Order By: Relevance
“…Moreover, Duarte et al (49) showed that functional brain activation can be influenced by impaired vascular coupling in patients with diabetes. Thus, we controlled the analyses for the individual vascularity as proposed by Tsvetanov et al (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Duarte et al (49) showed that functional brain activation can be influenced by impaired vascular coupling in patients with diabetes. Thus, we controlled the analyses for the individual vascularity as proposed by Tsvetanov et al (31).…”
Section: Resultsmentioning
confidence: 99%
“…We implemented the method by Tsvetanov et al (31) by using a scaling of the first-level contrast images by the individual resting state fluctuation amplitude before group analyses. Resting state measurements were analyzed using Data Processing Assistant for Resting-State fMRI running on Statistical Parametric Mapping 8 software (32).…”
Section: Imaging Procedures and Analysesmentioning
confidence: 99%
“…However, a recent study revealed that, although older adults did exhibit reduced CBF in comparison with younger adults, the uptake of oxygen, lactate, and glucose did not differ between the two age‐groups, suggesting that reduced CBF in older adults does not affect the brain's ability to uptake nutrients (Fisher et al., 2013). Although, others have reported that regionally specific age differences in physiological fluctuations exist, which may only partly reflect those captured on a global level (Tsvetanov et al., 2015). This means that global regression methods may not always be the most accurate method of physiological correction between age‐groups as any regional differences that deviate from the global pattern may be inadequately corrected for.…”
Section: Discussionmentioning
confidence: 99%
“…While all these methods were developed with the aim of improving group statistics by reducing inter-subject vascular variance, they should be considered for a valid assessment of neural individual differences (see Figure 3(c) [74]). As with any manipulation of the data, there are potential caveats: calibration and normalization methods may remove individual differences of neural origin, for instance if baseline blood oxygenation were linked to neural activity [62].…”
Section: Validity: Are Individual Differences Attributable To Brain Fmentioning
confidence: 99%
“…As with any manipulation of the data, there are potential caveats: calibration and normalization methods may remove individual differences of neural origin, for instance if baseline blood oxygenation were linked to neural activity [62]. Before such techniques are routinely applied, more examples of their successful application, ideally vetted by an independent measure of neural function [74], are needed.…”
Section: Validity: Are Individual Differences Attributable To Brain Fmentioning
confidence: 99%